Hochuekkito (TJ-41), a Kampo Formula, Ameliorates Cachexia Induced by Colon 26 Adenocarcinoma in Mice. (24th December 2012) - Yae, Suzu; Takahashi, Fumiyuki; Yae, Toshifumi; Yamaguchi, Takuji; Tsukada, Rika; Koike, Kengo; Minakata, Kunihiko; Murakami, Akiko; Nurwidya, Fariz; Kato, Motoyasu; Tamada, Mayumi; Yoshikawa, Momoko; et al.
Abstract : Cachexia, a major cause of cancer-related death, is characterized by depletion of muscle and fat tissues, anorexia, asthenia, and hypoglycemia. Recent studies indicate that secretions of proinflammatory cytokines such as interleukin-6 (IL-6) play a crucial role in cachexia development, and that these cytokines are secreted from not only cancer cells but also host cells such as macrophages. In this study, we investigated the therapeutic effects of hochuekkito, a Kampo formula, on cachexia induced by colon 26 adenocarcinoma in mice. Hochuekkito treatment did not inhibit tumor growth, but significantly attenuated the reduction in carcass weight, food and water intake, weight of the gastrocnemius muscle and fat tissue around the testes, and decrease of serum triglyceride level compared with controls. Furthermore, hochuekkito treatment significantly reduced serum IL-6 level and IL-6 expression level in macrophages in tissues surrounding the tumor. In vitro studies showed that hochuekkito suppressed the production of IL-6 by THP-1 or RAW264.7 macrophage cells, although it did not affect IL-6 production by colon 26 carcinoma cells. These results suggest that hochuekkito inhibits the production of proinflammatory cytokines, particularly IL-6, by host cells such as macrophages. Therefore, hochuekkito may be a promising anticachectic agent for the treatment of patients with cancer.